In vitro colonic fermentation of fermented Radix Astragali by Poria cocos and anti-hyperuricemia mechanism based on network pharmacology and experiment verification - Chen, Caiyun; Liu, Keyu; Wang, Yishu; Song, Xinru; Gao, Wenjing; Wang, Yanlin; Chen, Yuxin; An, Ziqi; Yin, Changting; Wang, Haiyan; Wang, Shaoping (Frontiers in Nutrition, 2024)
This research aims to probe the effects of fecal microbiota and Lactobacillus acidophilus on the metabolism of Radix Astragali (RA) and Poria cocos solid fermenting Radix Astragali (FRA). It further explores pharmacological effects of RA, Poria cocos and FRA on HUA mouse model and the mechanisms in HUA treatment. The results indicated that astragaloside IV (AG Ⅳ), total saponins and flavonoids continuously decreased in FRA and RA during 48 h fecal microbiota colonic fermentation. During Lactobacillus acidophilus fermentation, in FRA, the content of AG Ⅳpeaked at 12 h with a value of 1.14 ± 0.20 mg/g, total saponins and flavonoids reached the highest values 136.34 ± 6.15 mg/g at 12 h and 6.35 ± 0.06 mg/g at 6 h, AG Ⅳ and total saponins peaking of 0.63 ± 0.05 mg/g and 115.12 ± 4.12 mg/g at 12 h and 24 h in RA, respectively, and total flavonoids consecutively decreased. The counts of Lactobacillus acidophilus increased significantly in FRA compared with RA. Pharmacodynamic outcomes revealed that FRA effectively reduced blood levels of uric acid (UA), triglycerides (TG), xanthine oxidase (XOD), alanine aminotransferase (ALT) and aspartate transaminase (AST) in HUA mice, exerting protective effects on the liver and kidney. Network pharmacology showed that there were 93 common targets for RA, Poria cocos and HUA with the top 5 core targets tumor necrosis factor (TNF), signal transducer and activator of transcription 3 (STAT3), cysteinyl aspartate specific proteinase 3 (CASP3), jun proto-oncogene (JUN) and estrogen receptor 1 (ESR1). Molecular docking analysis revealed that AG Ⅳ, calycosin and formononetin bond well to the core targets. This research revealed the interaction of RA and FRA with fecal microbiota and Lactobacillus acidophilus, RA and Poria cocos were featured with multiple components, target points, and signaling pathways in HUA treatment, which provided fresh insights for further HUA therapeutics.